Answer:
![m = 10\sqrt 3](https://tex.z-dn.net/?f=m%20%3D%2010%5Csqrt%203)
![n = 10](https://tex.z-dn.net/?f=n%20%3D%2010)
Step-by-step explanation:
Required
Find m and n
Considering the given angle, we have:
![\sin(60) = \frac{Opposite}{Hypotenuse}](https://tex.z-dn.net/?f=%5Csin%2860%29%20%3D%20%5Cfrac%7BOpposite%7D%7BHypotenuse%7D)
This gives:
![\sin(60) = \frac{m}{20}](https://tex.z-dn.net/?f=%5Csin%2860%29%20%3D%20%5Cfrac%7Bm%7D%7B20%7D)
Make m ths subject
![m = 20 * \sin(60)](https://tex.z-dn.net/?f=m%20%3D%2020%20%2A%20%5Csin%2860%29)
![\sin(60) =\frac{\sqrt 3}{2}](https://tex.z-dn.net/?f=%5Csin%2860%29%20%3D%5Cfrac%7B%5Csqrt%203%7D%7B2%7D)
So, we have:
![m = 20 *\frac{\sqrt 3}{2}](https://tex.z-dn.net/?f=m%20%3D%2020%20%2A%5Cfrac%7B%5Csqrt%203%7D%7B2%7D)
![m = 10\sqrt 3](https://tex.z-dn.net/?f=m%20%3D%2010%5Csqrt%203)
Considering the given angle again, we have:
![\cos(60) = \frac{Adjacent}{Hypotenuse}](https://tex.z-dn.net/?f=%5Ccos%2860%29%20%3D%20%5Cfrac%7BAdjacent%7D%7BHypotenuse%7D)
This gives:
![\cos(60) = \frac{n}{20}](https://tex.z-dn.net/?f=%5Ccos%2860%29%20%3D%20%5Cfrac%7Bn%7D%7B20%7D)
Make n the subject
![n = 20 * \cos(60)](https://tex.z-dn.net/?f=n%20%3D%2020%20%2A%20%5Ccos%2860%29)
![\sin(60) =\frac{1}{2}](https://tex.z-dn.net/?f=%5Csin%2860%29%20%3D%5Cfrac%7B1%7D%7B2%7D)
So, we have:
![n = 20 *\frac{1}{2}](https://tex.z-dn.net/?f=n%20%3D%2020%20%2A%5Cfrac%7B1%7D%7B2%7D)
![n = 10](https://tex.z-dn.net/?f=n%20%3D%2010)
10+6x=4x-4
6x-4x=-4-10
2x=-14
x-7
10=6(-7)=-32
4(-7)-4=-32
=-32
<u>Answer:
</u>
The value of the exponential expression
is 2
<u>Solution:</u>
16 superscript one-fourth= ![16^{\frac{1}{4}}](https://tex.z-dn.net/?f=16%5E%7B%5Cfrac%7B1%7D%7B4%7D%7D)
As per the problem,
We have to find the value of
16 in terms of 2 can be written as ![2\times2\times2\times2](https://tex.z-dn.net/?f=2%5Ctimes2%5Ctimes2%5Ctimes2)
= ![(2 \times 2 \times 2 \times 2)^{\frac{1}{4}}](https://tex.z-dn.net/?f=%282%20%5Ctimes%202%20%5Ctimes%202%20%5Ctimes%202%29%5E%7B%5Cfrac%7B1%7D%7B4%7D%7D)
=![\left(2^{4}\right)^{\frac{1}{4}}](https://tex.z-dn.net/?f=%5Cleft%282%5E%7B4%7D%5Cright%29%5E%7B%5Cfrac%7B1%7D%7B4%7D%7D)
As per the exponential rule, ![a^{(m)^{n}}=a^{m \times n}](https://tex.z-dn.net/?f=a%5E%7B%28m%29%5E%7Bn%7D%7D%3Da%5E%7Bm%20%5Ctimes%20n%7D)
=![2^{4 \times \frac{1}{4}}](https://tex.z-dn.net/?f=2%5E%7B4%20%5Ctimes%20%5Cfrac%7B1%7D%7B4%7D%7D)
Here, ![4\times\frac{1}{4}=1](https://tex.z-dn.net/?f=4%5Ctimes%5Cfrac%7B1%7D%7B4%7D%3D1)
= ![2^{1}](https://tex.z-dn.net/?f=2%5E%7B1%7D)
= 2
Hence, the value is 2.
999.1 is the answer you multiply both then add
Answer:
so your answer is 52!!!
Step-by-step explanation:
Surface area is 2*l*h+2*l*w+2*w*h
Hope this helps
Pls mark brainleist
Thanks!!